The association between patterns of atrial fibrillation, anticoagulation, and cardiovascular events. Issue 2 (20th November 2019) - Atar, Dan; Berge, Eivind; Le Heuzey, Jean-Yves; Virdone, Saverio; Camm, A John; Steffel, Jan; Gibbs, Harry; Goldhaber, Samuel Z; Goto, Shinya; Kayani, Gloria; Misselwitz, Frank; Stepinska, Janina; et al.
Abstract: Aims: Guidelines do not recommend to take pattern of atrial fibrillation (AF) into account for the indication of anticoagulation (AC). We assessed AF pattern and the risk of cardiovascular events during 2-years of follow-up. Methods and results: We categorized AF as paroxysmal, persistent, or permanent in 29 181 patients enrolled (2010–15) in the Global Anticoagulant Registry In the FIELD of AF (GARFIELD-AF). We used multivariable Cox regression to assess the risks of stroke/systemic embolism (SE) and death across patterns of AF, and whether this changed with AC on outcomes. Atrial fibrillation pattern was paroxysmal in 14 344 (49.2%), persistent in 8064 (27.6%), and permanent 6773 (23.2%) patients. Median CHA2 DS2 -VASc, GARFIELD-AF, and HAS-BLED scores assessing the risk of stroke/SE and/or bleeding were similar across AF patterns, but the risk of death, as assessed by the GARFIELD-AF risk calculator, was higher in non-paroxysmal than in paroxysmal AF patterns. During 2-year follow-up, after adjustment, non-paroxysmal AF patterns were associated with significantly higher rates of all-cause death, stroke/SE, and new/worsening congestive heart failure (CHF) than paroxysmal AF in non-anticoagulated patients only. In anticoagulated patients, a significantly higher risk of death but not of stroke/SE and new/worsening CHF persisted in non-paroxysmal compared with paroxysmal AF patterns. Conclusion: In non-anticoagulated patients, non-paroxysmal AF patterns were associated with higher risks of stroke/SE, new/worsening HF and death than paroxysmal AF. In anticoagulated patients, the risk of stroke/SE and new/worsening HF was similar across all AF patterns. Thus AF pattern is no longer prognostic for stroke/SE when patients are treated with anticoagulants. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01090362.